Miejskie tajemnice. Paryż Eugeniusza Sue a Warszawa Adolfa Dygasińskiego = Urban Mysteries: Eugene Sue`s Paris and Adolf Dygasiński`s Warsaw - Lesicz-Stanisławska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article compares two urban texts - "The Mysteries of Paris" by Eugene Sue (treated as a modelnovel of city mysteries) and Adolf Dygasiński`s trilogy called "The New Mysteries of Warsaw". Thecomparison of these novels, which follow the scheme of the novel of city mysteries, allowed me tofind some clear similarities, for instance, the authors` desire to strengthen the mystery plot, andhence the reader`s involvement, to deepen the social dimension of the story, to depict phenomenathat correspond to the urbanization processes of civilization
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); Dygasiński, Adolf (1839-1902); literatura francuska - historia - 19 w.; literatura polska - historia - 19 w.